Control of the HIV-1 DNA Reservoir Is Associated In Vivo and In Vitro with NKp46/NKp30 (CD335 CD337) Inducibility and Interferon Gamma Production by Transcriptionally Unique NK Cells - Marras, Francesco (J Virol, 2017)
The size of lentiviral DNA reservoirs reflects the effectiveness of immune responses against lentiviruses. So far, abundant information has been gathered on the control of HIV-1 replication. Understanding the innate mechanisms contributing to containment of the HIV DNA reservoir, however, are only partly clarified and are relevant to guiding interventions for reservoir containment or eradication. We studied the contribution of natural killer (NK) cell functional features in HIV patients controlling replication either spontaneously (HIV controllers [HIC]) or after progression and antiretroviral treatment (progressor patients [PP]). An inverse correlation between HIV DNA copy numbers (either total or integrated) in circulating CD4(+) cells and NK cell function was observed. Induced interferon gamma (IFN-γ) production and NKp46/NKp30 activating receptor-induced expression correlated inversely with reservoir size. The correlation was present not only for a homogeneous cohort of HIC patients but also when PP were included in the analysis. Adaptive (NKG2C(+) CD57(+)) NK cell features were not associated with reservoir size. However, a distinct set of 370 differentially expressed transcripts was found to underlie functional differences in NK cells controlling HIV DNA reservoir size. In proof-of-principle in vitro experiments of CD4(+) cell infection with HIV-1, purified NK cells with the above-mentioned functional/transcriptional features displayed 10- and 30-fold higher abilities to control HIV replication and DNA burdens in vitro, respectively, than those of other NK cells. Thus, NK cells with a specific functional and transcriptional signature contribute to control of the HIV reservoir in CD4(+) cells. Their selection, expansion, and/or adoptive transfer may support strategies to eradicate HIV-1 infection or to safely deescalate antiretroviral treatment. IMPORTANCE The most relevant feature of HIV-1 infection is represented by its DNA reservoir size in the body, which guarantees lifelong infection and resumption of virus replication after antiretroviral treatment interruption. So far, there has been little success in the identification of factors contributing to HIV-1 reservoir containment. In this study, by studying quantitative total and integrated HIV-1 DNA levels and NK cells in HIV-1 patients with either progressive or nonprogressive disease, we observed that inducible IFN-γ and natural cytotoxicity receptor (NCR) expression in a specific subset of NK cells with a characteristic transcriptional signature represents a correlate for HIV-1 reservoir control. This represents an advance in our understanding of the mechanism(s) that controls the lentivirus reservoir. Monitoring, selection, expansion, and adoptive transfer of these NK cells may allow monitoring of treatment efficacy and the likelihood of reservoir control and may support protocols for HIV-1 eradication.